Банно-прачечное дело как рыночная услуга в Византии IV–IX вв. - Сорочан, С.Б. (My University, 2015)
The Bath-Laundry Business as a Market Service in Byzantium in the IV–IX Centuries by S.B.Sorochan (Kharkov, Ukraine) The article reviews the status of laundry and bath business in Byzantium from late antiquity to the IX century, when the empire became a typical medieval state with Christian society. The author comes to the conclusion that in the early Byzantine period laundry business has ceased its function as a market service industry. But bath business experienced a complex evolution and had no significant decline after the VI century. This is contrary to current views about the disappearance of Byzantine baths and bath attendant profession, stoker baths in the “dark ages”. Bath business restructuring took place in a different plane. Because of the complex reasons the Byzantine capital baths lost their former luxury, large sizes. In the provinces, they also became smaller. alongside with enfilade type baths, another baths were built with the absence of symmetry, where the main and sometimes the only place caldarium occupied. However, such facilities took place in the Byzantine city through the centuries. They stopped being an entertainment centers and became an ordinary establishments for washing to comply with the hygiene and Christian piety.